Photocatalytic degradation of contaminants of emerging concern using a low-cost and efficient black bismuth titanate-based water treatment reactor. (February 2022) - Grao, Matthieu; Redfern, James; Kelly, Peter; Ratova, Marina
Abstract: Photocatalysis is recognized as a sustainable technology for wastewater treatment, but it is limited by its scalability and efficiency. Here, we report the fabrication of a bespoke photocatalytic reactor, made from readily available consumer market components. The reactor was loaded with glass rods coated with a bismuth titanate photocatalyst deposited by reactive pulsed DC magnetron sputtering. Bismuth titanate is a remarkable material, which has shown the property of increasing its photocatalytic capabilities over repeated usage due to photoinduced oxygen vacancies, forming oxygen-vacancy rich "black" bismuth titanate. The reactor was tested with different rod configurations and photocatalytic material was cycled over 25 times, equivalent to 125 h of consecutive use, against methylene blue dye under UV light. Orange II dye degradation tests carried out in the presence of scavengers revealed that photocatalytic reactions were driven by superoxide ( O 2 ∙− ) and holes ( h + ), when using pristine bismuth titanate and by superoxide ( O 2 ∙− ), electrons ( e − ) and holes ( h + ), when using "black" bismuth titanate. Finally, the reactor was used to successfully degrade levofloxacin, a typical antibiotic, which was verified by UV–Vis (ultraviolet-visible) spectroscopy and inhibition zone tests in the presence of three different pathogens ( E. coli, S. aureus and A. baumannii ). Graphical abstract: Unlabelled Image Highlights: An affordable photocatalytic reactor was built from consumer market components. The reactor was loaded with glass rods coated by reactive magnetron sputtering with a bismuth titanate photocatalyst. Activity of bismuth titanate increases with repeated use, due to photoinduced oxygen vacancies. The photocatalytic reactor was able to nullify the antibacterial potency of levofloxacin in 24 h experiment.